Photobiomodulation Therapy for Neurosensory Disturbances in Orthognathic Surgery Patients: A Systematic Review - Aneta Olszewska; Mateusz Wolny; Julia Kensy; Agnieszka Kotela; Agata Czajka-Jakubowska; Jacek Matys (Life)
Background: Sensory disturbances and acquired paresthesia constitute a significant proportion of complications following orthognathic surgery. This systematic review examines the application of photobiomodulation (PBM) in managing these complications and its efficacy in promoting sensory recovery. Methods: In November 2024, a comprehensive digital search was performed across reputable databases, including PubMed, Web of Science, and Scopus, using carefully selected search terms: “orthognathic surgery” AND (physiotherapy OR physical therapy OR laser OR LLLT OR PBM OR light OR LED OR acupuncture) AND (nerve OR neurosensory OR paresthesia). The search adhered to the PRISMA guidelines. Of the 424 articles initially identified, 14 met the inclusion criteria and were included in the review. Results: The review focused on diode laser therapy for treating inferior alveolar nerve injuries, with most studies targeting this nerve and exploring diverse wavelengths, protocols, and surgical contexts, including orthognathic surgeries. Significant improvements were observed in tactile sensitivity, pain perception, and mechanical responsiveness. Factors such as earlier initiation of therapy, younger patient age, and higher treatment frequency were associated with improved outcomes. Conclusions: Low-level laser therapy emerges as a safe and effective intervention for enhancing neurosensory recovery following orthognathic surgery. However, the development of standardized treatment protocols and the conduct of larger-scale clinical trials are essential to optimize their clinical application.